Small molecule inhibitors of cyclin-dependent kinase 9 for cancer therapy - Aisha Alsfouk (Taylor & Francis Group, 2021)
Cyclin-dependent kinase 9 (CDK9) plays a vital role in transcription through regulation of short-lived anti-apoptotic genes required for cancer cell survival. Therefore, targeting CDK9 with small molecule inhibitors has emerged as a potential cancer therapy. This article reviews the most recent CDK9 patent literature (2012-2020) related to small molecule inhibitors in cancer along with their selectivity profile and biological results in preclinical studies.